Ilmu Sosial Transformatif - Purwo Santoso (Millah: Journal of Religious Studies, 2012)
Social science which is intended in this paper covers a variety of disciplines, including sociology, political science, economics, anthropology, history, law and so on. The term transformative in the sense used here are loose, just to indicate how the scientists are not only struggling to answer the questions themselves, but the bother and in turn devote his dedication to the community to answer the questions. Development of a transformative social science requires expertise in three-dimensional philosophy of science: the ontology, epistemology, and axiology. Transformative character is also determined by the axiology choice. Social science were developed not only for development or accumulation of theory but also to improve the social relations that existed, to produce a social reality which was considered better.